Successful treatment of radiotherapy and apatinib in patient with mediastinal mixed non-seminomatous germ cell tumor: A case report. Issue 43 (29th October 2021) - Ren, Congcong; Zhao, Jing; Kang, Lin; Di, Yan; Qiu, Gang; Wang, Qingxue
Abstract: Rationale: Mediastinal non-seminomatous germ cell tumors (MNSGCTs) are rare malignancies. Chemotherapy followed by surgical resection has been regarded as the standard management, but treatment options for chemotherapy-refractory patients or those with unresectable tumors are limited, resulting in a very poor prognosis. Patient concerns: An 18-year-old female presented with symptoms of cough, chest tightness, and shortness of breath for 2 months, and the symptoms gradually worsened. Diagnosis: Computed tomography (CT) revealed a large mediastinal mass invading the pericardium and great blood vessels. Serum human chorionic gonadotropin (HCG) and α-fetoprotein (AFP) levels were normal. Histopathological examination of biopsy specimens revealed mixed MNSGCT with embryonal carcinoma and immature teratoma components. Interventions: The patient achieved complete remission (CR) and long-term survival after multimodal therapy comprising chemotherapy, positron emission tomography/CT (PET/CT)-guided volumetric-modulated arc therapy (VMAT), and anti-angiogenic targeted therapy. Outcomes: The patient was followed up for more than 4 years without recurrence, metastasis, or treatment-related adverse effects. Lessons: The case presented here highlights the importance of multidisciplinary diagnosis and treatment, providing evidence that radiotherapy and anti-angiogenic therapy may play an important role in unresectable or residual tumors after failure of conventional treatments of MNSGCT. Percutaneous biopsy is necessary for diagnosis if the tumor is unresectable, and serum AFP and HCG levels are normal. Additionally, PET/CT is an effective method for evaluation of efficacy and radiotherapy guidance for patients with MNSGCTs.